O perfil antropométrico e hábitos de vida de pessoas com síndrome de Down matriculadas em instituições de referência - Souza, Paula Ribeiro de (2020)
Down syndrome (DS) is a more common chromosomal disorder that affects the population with intellectual impairment. This genetic condition causes the individual to present specific characteristics that compromise his nutritional status and increase the chance of overweight, obesity and development of cardiovascular diseases. In this way, people with DS need extra care, changes in their eating habits and quality of life. Care with nutritional status and food increases the survival of individuals with Down syndrome, decreasing associated comorbidities in DS. This research aims to characterize the anthropometric profile of life habits of people with Down syndrome. This is a cross-sectional descriptive study. A sample consisted of 80 people with DS, enrolled in reference institutions, aged ≥ seven years old, of both sexes and with the authorization of their guardians. A statistical analysis was performed with the program Stata SE 12.0. Data collection takes place with an elaborated sociodemographic questionnaire, a validated Food Frequency Questionnaire (FFQ) and anthropometric instruments (scale with stadiometer and measuring tape). In the analyzes, a 95% confidence interval was adopted. Most of the participants were male, aged less than or equal to 20 years, were breastfed and were sedentary. Overweight was higher in adults, as well as waist circumference, considerably higher in men, increasing the risk of developing chronic non-communicable diseases. Most participants had some disease associated with DS, the most common being: hypothyroidism and corrected cardiac changes. Most participants were male, aged ≤ 20 years, were breastfed and were sedentary. Overweight was higher in adults and waist circumference, considerably higher in men, increased the risk of developing chronic diseases. The majority had some disease associated with DS, the most common being hypothyroidism. There were no strong correlations between food and anthropometric data. An increase in body mass, BMI and AC was found with aging, mostly in males. People with DS and associated hypothyroidism have higher BMI and WC. While the consumption of some foods may contribute to an increase in BMI, it was not possible to infer dependence between food and physical activity.